Institutional and Students’ Factors Influencing Adoption of E-Learning in Higher Educational Institutions in Kenya: A Case of Public Universities - Wanjara, Amos Otieno; Ogembo, Paul Okeyo (Universitas Pendidikan Ganesha, 2024)
E-learning as a crucial aspect of ICT is a new model of education dispensation in the Higher Educational Institutions (HEIs) across the world. However, this technologically enhanced educational model is still at the infancy stage in the developing countries, Kenya not exceptional. The purpose of the study was to assess the institutional and students’ factors influencing adoption of e-learning in Higher institutions of Learning in Kenya. The specific objectives were: to establish the impact of institutional e-learning policy (IEP) on its adoption in HEIs in Kenya, to establish the impact of lecturers’ perceived ease of use (PEU) of e-learning on its adoption in HEIs and to establish effect of students’ perceived usefulness (PU) of e-learning on its adoption in HEIs. The study was underpinned by Technology Acceptance Model. This study reviewed 69 relevant empirical literatures whose meta- analysis was guided. The study established that lecturers’ perceived ease of use of e-learning affects its adoption, that institutional e-learning policy has significant relationship with e-learning adoption and that students’ e-learning perceived usefulness has a great effect on its adoption in the university. The study findings have implications on close scrutiny of universities’ e-learning policies toward its implementation; on provision of e-pedagogical training to lecturers toward e-learning capacity building; implications on universities’ ICT Departments’ preparation of students for e-learning educational model. In a nutshell the study finding would inform the best organizational practices towards e-learning effectiveness.